2020
DOI: 10.3390/catal10111244
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Influence on Selectivity in α-Pinene Oxide Isomerization Using MoO3-Modified Zeolite BETA

Abstract: Natural source turpentine is an available source of α-pinene oxide. This compound’s value is especially given by the possibility of producing important compounds campholenic aldehyde and trans-carveol. In this work, we would like to present the usage of MoO3-modified zeolite BETA in α-pinene oxide isomerization concerning campholenic aldehyde and trans-carveol formation using a wide range of solvents. Catalyst calcination temperature also influenced the reaction course (selectivity to desired compounds and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Moreover, high selectivity to TCV can be linked to an easier proton transfer to the tertiary cation in the presence of a basic solvent, such as N , N -dimethylacetamide applied in the current work. On the contrary, for nonpolar and nonbasic solvents, selectivity to campholenic aldehyde is elevated …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, high selectivity to TCV can be linked to an easier proton transfer to the tertiary cation in the presence of a basic solvent, such as N , N -dimethylacetamide applied in the current work. On the contrary, for nonpolar and nonbasic solvents, selectivity to campholenic aldehyde is elevated …”
Section: Resultssupporting
confidence: 93%
“…It was suggested that the formation of trans -carveol over Lewis acid sites (Scheme ) occurs through formation of a tertiary cation C′, similar to cation C in Scheme , which was supposed to be more stable than a secondary cation of type A′. Moreover, high selectivity to TCV can be linked to an easier proton transfer to the tertiary cation in the presence of a basic solvent, such as N , N -dimethylacetamide applied in the current work. On the contrary, for nonpolar and nonbasic solvents, selectivity to campholenic aldehyde is elevated …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Solvent influence on the course of any reaction can be crucial [36]. The solvent influence on our reaction is visible in Table 6, rows 6-10.…”
Section: Influence Of the Solventmentioning
confidence: 99%